On 𝔉-radicals of finite π-soluble groups - Guo, W.; Xi Liu; Baojun Li (Algebra and Discrete Mathematics, 2006)
In this paper, we prove that for every local πsaturated Fitting class 𝔉 with char(𝔉) = P, the F-radical of every finite π-soluble groups G has the property: CG(G𝔉 ) ⊆ G𝔉 . From this, some well known results are followed and some new results are obtained.